A DFT Mechanistic Study of the Regio-, Chemo-, and Stereo- Selectivities of the (3 + 2) Cycloaddition of Diarylnitrone Derivatives with 1-(4-Nitrophenyl)-5H-Pyrrolin-2-One - Sylvia Adomako; Joshua Atta-Kumi; Cecil H. Botchway; Richard Tia; Evans Adei; Albert Aniagyei (Journal of Chemistry)
Heterocyclic compounds are vital in rational drug design by providing convenient means for the optimization of drugs or drug candidates. Isoxazolidine (a heterocyclic compound) derived from the (3 + 2) cycloaddition reaction is reported to possess anticancer, antiviral, antibacterial, and anti-inflammatory properties. The mechanistic study of the chemo-, regio-, and stereo-selectivities of the (3 + 2) cycloaddition reaction (32CA) of diarylnitrones (A1) to 1-(4-nitrophenyl)-5H-pyrrolin-2-one (A2) has been conducted using the density functional theory (DFT) method at the M06/6-311G (d, p) computational level. The 32CA reaction of A1 and A2 proceeds through a chemo-selective addition of A1 across the C=C olefinic bond of A2 to furnish both kinetically and thermodynamically favored reaction routes. The effect of substitution on the 32CA reaction has been studied using a representative set of electron-acceptor and electron-releasing groups on both A1 and A2. The chemo-, regio-, and stereo-selectivities observed in the 32CA reaction remained unchanged irrespective of the substituents used on both reactants, but a change in kinetics and thermodynamics was observed based on the substituents. In the 32CA reaction of A1 and A2, the “exo” cycloadduct formation was favored over the “endo” cycloadducts in all instances.